2023
DOI: 10.1186/s12875-023-01974-1
|View full text |Cite
|
Sign up to set email alerts
|

Effective web-based clinical practice guidelines resources: recommendations from a mixed methods usability study

Abstract: Background Clinical practice guidelines (CPG) are an important knowledge translation resource to help clinicians stay up to date about relevant clinical knowledge. Effective communication of guidelines, including format, facilitates its implementation. Despite the digitalization of healthcare, there is little literature to guide CPG website creation for effective dissemination and implementation. Our aim was to assess the effectiveness of the content and format of the Diabetes Canada CPG websit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The exception is a study of simulated rather than actual practice, which identified 21 guidelines-use discrepancies contributing to a medication error, of which 14 discrepancies related to finding the guideline and seven discrepancies related to reading it [ 14 ]. Similarly, previous user testing studies have identified problems finding and understanding information in guidelines, but were not designed to investigate a subsequent contribution to medication errors [ 19 , 20 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exception is a study of simulated rather than actual practice, which identified 21 guidelines-use discrepancies contributing to a medication error, of which 14 discrepancies related to finding the guideline and seven discrepancies related to reading it [ 14 ]. Similarly, previous user testing studies have identified problems finding and understanding information in guidelines, but were not designed to investigate a subsequent contribution to medication errors [ 19 , 20 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…While iterative user testing and subsequent modification has been shown to make it easier for health professionals to find and understand information within one specific guideline [ 19 , 20 , 27 ], it does not address the process of finding the correct guideline to use, which contributed to many of incidents reported in the present study. Future research should therefore investigate whether techniques such as iterative usability testing of wider guideline information systems [ 28 ] are able to prevent further medication errors. Given the limitations of research based on voluntary reporting of medication incidents, future studies utilising prospective qualitative or quantitative data collection from staff involved in incidents would give greater certainty about the characteristics and prevalence of guideline-related medication errors.…”
Section: Discussionmentioning
confidence: 99%
“…After the CRCweb prototype is developed, we will ask 4 patient-caregiver dyads to use the CRCweb prototype and provide feedback about the usability of the program [ 34 ]. Semistructured interviews (30-45 minutes) will probe for participants’ experiences with using CRCweb (eg, design, navigation, structure, and language).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the proven benefits, implementation rates remain below 50% historically across clinical disciplines [ 4 , 34 ]. Many attempts have been made to identify barriers that limit the implementation of clinical guidelines in daily medical practice [ 35 , 36 ]. It has been found that many guideline manuals are too long and complicated, making it difficult to implement them effectively.…”
Section: Hesitancy In Delivering a New Antidiabetic Drug Treatment St...mentioning
confidence: 99%
“…Given the abundance of guidelines available, there is a growing need for continuous quality assessment and the improvement of the development process [ 8 , 34 , 35 ]. In today’s era of healthcare system digitalization, online tools such as websites, alerting systems, interactive platforms and clinical decision support systems are being used to aid in the access and implementation of clinical guidelines [ 36 , 37 , 38 ]. However, the effects on practice and clinical outcomes from these tools are still unknown.…”
Section: Hesitancy In Delivering a New Antidiabetic Drug Treatment St...mentioning
confidence: 99%